Management and Development of Productive Waqf for Islamic Boarding Schools in Kampar Regency - Suyatno, Suyatno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to explore the management and development of productive waqf and its strategies in Islamic boarding schools in Kampar Regency, Riau Province. Waqf is an integral part of the dynamics of Islamic boarding schools. This study is a field research conducted using a qualitative descriptive approach. Data collection with observation, interviews, and Focus Group Discussion. The data were analyzed using the Qualitative Data Analysis approach with NVivo 12 Plus software. In managing its waqf assets, the Foundation relies on strengthening the organizational system by improving the quality of the nazhir, management of administrative tasks and waqf asset inventory, as well as organizational management. The Waqf Foundation of Al-Ihsan Riau manages waqf through money and cash waqf and develops productive waqf by establishing business units, including Ahsanta Mart, Ahsanta Cafe, Ahsanta Agro, IBS Business Center, Sharia microfinance, and LPG gas stations. To maintain the existence of waqf assets and the sustainability of their benefits, the foundation uses the following strategies: first, building transparency and accountability. Second, optimizing waqf through money is an instrument for accelerating infrastructure and facility development. Third, optimizing cash waqf as an instrument for business development and the independence of the Islamic boarding school. Fourth, optimizing zakat and donation programs for scholarships and human resource development. Fifth, building a waqf ecosystem and partnerships with economic protection policies. The foundation’s assets are charitable waqf aimed at implementing religious education based on Islamic boarding school principles. The benefits of waqf include organizing education based on Islamic boarding schools as the main core competence. This includes nurturing more than 30 mosques and prayer rooms around the Islamic boarding school, providing scholarships to 289 students, collaborating with preachers, utilizing waqf infrastructure for various religious, social, and community activities, providing healthcare services to the Islamic boarding school, and empowering the economy through partnerships and consignment patterns with the surrounding community.